A 3D porous FeP/rGO modulated separator as a dual-function polysulfide barrier for high-performance lithium sulfur batteries. Issue 3 (22nd November 2019) - Zhang, Yingge; Wang, Yange; Luo, Rongjie; Yang, Ya; Lu, Yang; Guo, Yan; Liu, Xianming; Cao, Shixun; Kim, Jang-Kyo; Luo, Yongsong
Abstract : A strong physical and chemical synergistic adsorption-catalysis-functional effect from FPG was confirmed via comprehensive experiments and theoretical analysis within LSBs. Abstract : Lithium–sulfur batteries (LSBs) have gained considerable attention for their desirable energy densities, high theoretical capacities, low cost and environmentally friendly properties. However, the shuttle effect of polysulfides seriously hinders their future practical applications. Herein, a dual-function cathode structure, consisting of 3D porous FeP/rGO microspheres supported on both aluminum foil and a commercial separator, exhibits excellent performance by providing strong adsorption with respect to Li2 S x ( x = 1, 2, 4, 6 and 8) and S8 . In this rational design, the iron phosphide (FeP) nanoparticles act as a catalyst to accelerate polysulfide conversion and as the designated sites for adsorption. The 3D rGO porous conductive network can provide enough space for sulfur loading and to physically adsorb the polysulfides. More importantly, density functional theory (DFT) calculations also verified the strong interactions (with adsorption energy values of −4.21 to −1.97 eV) between the FeP(111) surface and the sulfur species. The electrochemical results show that the cell using the dual-function cathode structure delivers a capacity of 925.7 mA h g −1, with capacity degradation of 0.05% per cycle after 500 cycles, at a current density of 0.5C. It is also worth mentioning that the cell with sulfur loading of ∼2.2 mg cm −2 maintained a high capacity of 483 mA h g −1 at 0.5C after 500 cycles. In summary, the above results demonstrate the promising application of the dual-function cathode structure for high-performance LSBs.